Paper Fiber Reinforced Foam Concrete Wall Paneling System - Fadila, Rahyan; Suleiman, Mohd Zailan; Md. Noordin, Norizal (2008)

(untitled)
One type of a new product for the usefulness of panel wall material containing mixed composite of cement, sand, and recycle paper called as Paper Fiber Reinforced Foam Concrete (PFRFC) as upon of the reinforcement addition is expected can improve materials quality for non load bearing wall.